2015
DOI: 10.1007/978-3-319-18787-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Landscape Runoff Water Quality Modelling: A Review

Abstract: As the recognition of the concept 'Sustainable Development' is increasing throughout the world, understanding the adverse impact of water quality parameters is highly important for the protection and improvement of aquatic environments from the impact of pollution. Therefore, the measurement of water quality parameters is required to protect and improve aquatic environments from the impact of pollution. The estimation of water quality parameters from direct field measurement is costly, time-consuming and somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…These hazardous events include accidents such as tanker spills (chemical hazards) and sewer overflows (microbial hazards) which can lead to a highly concentrated point-source of pollutants entering the harvesting system. Hossain and Imteaz [11] reported that vehicular transport is the major source of spills to the surface waters. There have been some studies investigating scenarios of hazard travel time in natural drainage systems.…”
Section: Introductionmentioning
confidence: 99%
“…These hazardous events include accidents such as tanker spills (chemical hazards) and sewer overflows (microbial hazards) which can lead to a highly concentrated point-source of pollutants entering the harvesting system. Hossain and Imteaz [11] reported that vehicular transport is the major source of spills to the surface waters. There have been some studies investigating scenarios of hazard travel time in natural drainage systems.…”
Section: Introductionmentioning
confidence: 99%